2023
DOI: 10.3389/fgene.2023.1107468
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brahman genetics on skin histology characteristics with implications for heat tolerance in cattle

Abstract: Cattle lose heat predominantly through cutaneous evaporation at the skin-hair coat interface when experiencing heat stress. Sweating ability, sweat gland properties, and hair coat properties are a few of the many variables determining the efficacy of evaporative cooling. Sweating is a significant heat dissipation mechanism responsible for 85% of body heat loss when temperatures rise above 86⁰F. The purpose of this study was to characterize skin morphological parameters in Angus, Brahman, and their crossbred ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…The level of biological variation identified in this study within a relatively uniform groups of cattle suggests a range of genetic potential that, if strategically targeted through selection and management, could lead to significant improvements on these traits for heat stress management. This biological diversity is similar to that found in a population ranging from 100% Angus to 100% Brahman, where a coefficient of variation of 49.77% was found for sweat gland area across five breed groups [ 8 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The level of biological variation identified in this study within a relatively uniform groups of cattle suggests a range of genetic potential that, if strategically targeted through selection and management, could lead to significant improvements on these traits for heat stress management. This biological diversity is similar to that found in a population ranging from 100% Angus to 100% Brahman, where a coefficient of variation of 49.77% was found for sweat gland area across five breed groups [ 8 ].…”
Section: Discussionsupporting
confidence: 83%
“…As air temperatures reach 30 °C, evaporative cooling by sweating is the primary mechanism for heat dissipation in cattle, however, some breeds have a greater potential for heat loss than others [ 4 ]. Recent research identified significant differences in skin properties related to heat exchange ability between Brahman and Angus cattle [ 8 ]. Studies on the possible genetic control of natural variations in sweat gland properties in beef cattle are not currently available.…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to physiological and morphological modifications that crossbred animals experience in comparison to their exotic parents, which help them adapt to hot, humid environments that are typically characterized by high temperatures and humidity. Such changes include changes in body size, hair coat, hide texture, and hematological characteristics, which allow them to have unique features that allow them to regulate their body temperature more effectively, resulting in less heat stress than pure Bos taurus [50]. In contrast to Boran cattle, exotic breeds lack natural resistance to tropical diseases like Anaplasmosis, Theileriosis, Cowdriosis, and other parasites and diseases transmitted by ticks.…”
Section: Effect Of Genotype On Calves' Survivabilitymentioning
confidence: 99%
“…Research shows that high or very low temperatures tend to hinder thermoregulation, leading to various physiological reflexes, such as increased heart and respiratory rates, sialorrhea and metabolic or reproductive problems, such as an increase in cortisol, glucose and a reduction in the animals’ digestion process, as well as a reduction in the quality of female oocytes and spermatogenesis, causing losses. In this sense, cattle regulate the excess solar radiation that comes into direct contact with their bodies by seeking shade, shelter or water to mitigate heat stress [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%